Spatial variation of soil bacteria communities and its alpha diversity as a potential bioindicator of land degradation - Muhammad Yusuf; Adji Ahmad Rinaldo Fernandes; Syahrul Kurniawan; Endang Arisoesilaningsih (Brawijaya University, 2021)
This study aimed at determining the community structure and diversity of soil bacteria in several land-use changes as an environmental bioindicator. This research was conducted in areas of intensive agriculture (PI), monoculture abandoned old-coffee plantation (KTT), mixed-young coffee plantation (HLS), and secondary forest/reference site (RS) in UB Forest (UBF) area, Malang, Indonesia. Soil samples were taken as a composite at three different points in each area using a soil ring at a depth of 0-20 cm. The 16S rRNA gene was used to determine the community structure, species richness, diversity, and ecological index (Chao1, Shannon, Simpson, ACE) of soil bacteria using the NGS approach. Statistical data were analysed using R and QIIME software. The community structure of soil bacteria at the phylum level displayed the same pattern in all study sites where Proteobacteria, Acidobacteria, Actinobacteria, Chloroflexi were the dominant groups. Conversely, the bacterial composition showed differences between study sites at the genus level. Alpha diversity in agricultural areas (PI, KTT, and HLS) was higher than forest area (RS), but it was not followed by bacterial beta diversity. The distinct soil bacteria composition and diversity were influenced by the physicochemical of soil properties in the studied area. Therefore, several bacterial taxa suggested being a potential bioindicator of forest soil degradation due to land-use change in this study. Soil bacterial indicators can be utilized to evaluate or monitor alteration of soil quality in terms of forest restoration or rehabilitation.